Genetic associations of hemoglobin in children with chronic kidney disease in the PediGFR Consortium - Atkinson, Meredith A.; Wühl, Elke; Schaefer, Franz (Pediatric research, 2019)
Genome-wide association studies (GWAS) in healthy populations have identified variants associated with erythrocyte traits, but genetic causes of hemoglobin variation in children with CKD are incompletely understood. The Pediatric Investigation of Genetic Factors Linked with Renal Progression (PediGFR) Consortium comprises three pediatric CKD cohorts: Chronic Kidney Disease in Children (CKiD), Effect of Strict Blood Pressure Control and ACE Inhibition on the Progression of CRF in Pediatric Patients (ESCAPE), and Cardiovascular Comorbidity in Children with CKD (4C). We performed cross-sectional and longitudinal association studies of single-nucleotide polymorphisms (SNPs) in 1125 patients. Children of European (n = 725) or Turkish (n = 400) ancestry (EA or TA) were included. In cross-sectional analysis, two SNPs (rs10758658 and rs12718597) previously associated with RBC traits were significantly associated with hemoglobin levels in children of EA and TA. In longitudinal analysis, SNP rs2540917 was nominally associated with hemoglobin in EA and TA children. SNPs associated with erythrocyte traits in healthy populations were marginally significant for an association with hemoglobin. Further analyses/replication studies are needed in larger CKD cohorts to investigate SNPs of unknown significance associated with hemoglobin. Functional studies will be required to confirm that the observed associations between SNPs and clinical phenotype are causal.